Cultures of legality : judicialization and political activism in Latin America - Couso, Javier, 1964-; Huneeus, Alexandra, 1967-; Sieder, Rachel (Cambridge studies in law and society., 2010)
"This volume explores the changing legal ideas and practices that accompany, cause, and are a consequence of the judicialization of politics in Latin America"--Provided by publisher